The Effectiveness of Metacognitive Strategies in Enhancing Students' Reading Skills in Islamic Economics: A Cross-Sectional Study - Parangu, Kaukabilla Alya; Wibowo, Amiruddin Hadi; Agustina, Eliasanti; Rizkiyah, Faiqotur (Universitas PGRI Madiun, 2023)
This study aimed to determine the effectiveness of metacognitive strategies in enhancing students' reading skills. The sample consisted of 50 Islamic Economics majors selected through random cluster sampling from 100 undergraduate EFL majors studying at different universities in East Java. The participants were randomly assigned to either the experimental group (N=50) or the control group. Five main instruments were used in the study: the Survey of Reading Strategies (SORS), Motivated Strategies for Learning Questionnaire (MSLQ), semi-structured interviews, a background questionnaire, and a reading comprehension test. The experimental group did much better on the posttest for reading comprehension (M=31.96, SD=10.56) than the students in the control groups. The results of this study are important for students, teachers, and people who make tools for teaching English as a second language.